Perlindungan Hukum Terhadap Layanan Kesehatan Masyarakat Kota Pekanbaru Berdasarkan Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Wan Agusti (Jurnal Hukum Respublica, 2020)
Protection and law enforcement in the field of health for the people of Pekanbaru City is clearly still lacking, many people complain about the protection of health. So that in this study will be discussed about how the legal protection of public health services in the city of Pekanbaru based on Law Number 36 of 2009 concerning Health. This type of research is sociological, so the data source used is primary data from interviews, secondary data from libraries and tertiary data from dictionaries, media, and encyclopedias. Data collection techniques are done by observation, interviews, and literature review.